The Impact of Lateral Gene Transfer in Chlamydia - Marti, Hanna; Suchland, Robert J.; Rockey, Daniel D. (Frontiers in Cellular and Infection Microbiology, 2022)
Lateral gene transfer (LGT) facilitates many processes in bacterial ecology and pathogenesis, especially regarding pathogen evolution and the spread of antibiotic resistance across species. The obligate intracellular chlamydiae, which cause a range of diseases in humans and animals, were historically thought to be highly deficient in this process. However, research over the past few decades has demonstrated that this was not the case. The first reports of homologous recombination in the Chlamydiaceae family were published in the early 1990s. Later, the advent of whole-genome sequencing uncovered clear evidence for LGT in the evolution of the Chlamydiaceae, though the acquisition of tetracycline resistance in C. suis is the only recent instance of interphylum LGT. In contrast, genome and in vitro studies have shown that intraspecies DNA exchange occurs frequently and can even cross species barriers between closely related chlamydiae, such as between C. trachomatis, C. muridarum and C. suis. Additionally, whole-genome analysis led to the identification of various DNA repair and recombination systems in C. trachomatis, but the exact machinery of DNA uptake and homologous recombination in the chlamydiae has yet to be fully elucidated. Here, we reviewed the current state of knowledge concerning LGT in Chlamydia by focusing on the effect of homologous recombination on the chlamydial genome, the recombination machinery, and its potential as a genetic tool for Chlamydia.